The conserved central domain of yeast U6 snRNA: importance of U2-U6 helix Ia in spliceosome assembly. - Ryan, Daniel E (2002)
In the pre-mRNA processing machinery of eukaryotic cells, U6 snRNA is located at or near the active site for pre-mRNA splicing catalysis, and U6 is involved in catalyzing the first chemical step of splicing. We have further defined the roles of key features of yeast U6 snRNA in the splicing process. By assaying spliceosome assembly and splicing in yeast extracts, we found that mutations of yeast U6 nt 56 and 57 are similar to previously reported deletions of U2 nt 27 or 28, all within yeast U2-U6 helix Ia. These mutations lead to the accumulation of yeast A1 spliceosomes, which form just prior to the Prp2 ATPase step and the first chemical step of splicing. These results strongly suggest that, at a late stage of spliceosome assembly, the presence of U2-U6 helix Ia is important for promoting the first chemical step of splicing, presumably by bringing together the 5' splice site region of pre-mRNA, which is base paired to U6 snRNA, and the branchsite region of the intron, which is base paired to U2 snRNA, for activation of the first chemical step of splicing, as previously proposed by Madhani and Guthrie [Cell, 1992, 71: 803-817]. In the 3' intramolecular stem-loop of U6, mutation G81C causes an allele-specific accumulation of U6 snRNP. Base pairing of the U6 3' stem-loop in yeast spliceosomes does not extend as far as to include the U6 sequence of U2-U6 helix Ib, in contrast to the human U6 3' stem-loop structure.